(untitled) (Revista de Administração, 2006)
The main motivation for this study was to examine and question the evolution of the theoretical, normative and practical accounting framework for business combinations in the North-American market, as the models issued by this country basically sustain disclosure models adopted by the European Union and various other countries. The North-American tradition of advanced studies in accounting standards and practices, associated with the constant need for accounting to adapt to economic practices (business combinations), has made this country develop a theoretical and normative accounting framework for business combinations that is unsurpassed until today. Our analysis included both the earliest editions of the main pronouncements related to the Generally Accepted Accounting Principles in the United States (US-GAAP) and the recent standards issued by the FASB in 2001, more specifically SFAS n.141 and SFAS n.142. After a series of different accounting techniques for business combinations, the FASB pronouncement (SFAS n.141) that substituted for APB Opinion n.16 (Business Combinations) and eliminated the use of the Pooling of Interests Method, turned the US-GAAP more consistent with other countries. accounting standards. The FASB pronouncement (SFAS n.142) that substituted for APB Opinion n.17 (Intangible Assets) stands out because it approximated the accounting treatment of goodwill, which is determined in the combinations accounted for by the Purchase Method, to its true economic essence. This study detected that, over time, certain accounting practices in the United States as well as in Brazil were aimed at manipulating financial indicators and results. Like in the past, recent changes by the standardizing body (FASB) were urged by, among other reasons, the intention to restrict the above mentioned manipulations by companies involved in business combinations.